2009
DOI: 10.1002/cncr.24716
|View full text |Cite
|
Sign up to set email alerts
|

The role of postoperative radiotherapy for the treatment of gangliogliomas

Abstract: BACKGROUND: Because of their rarity, no prospective studies have been performed regarding gangliogliomas. The optimal treatment regimen is unclear. In this study, the authors compared 4 therapies for local control (LC) and overall survival (OS) in patients with ganglioglioma. METHODS: In 402 patients with ganglioglioma, outcomes were compared for patients who underwent gross total resection alone (GTR) (n ¼ 188), GTR plus radiotherapy (GTR þ RT) (n ¼ 21), subtotal resection alone (STR) (n ¼ 113), and STR plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 145 publications
5
44
0
Order By: Relevance
“…Doses greater than 50 Gy are frequently recommended for local control [15,20]. Prescribed doses for pediatric AGGs ranged between 50 and 63 Gy, but Rades et al [[8]] found that dose escalation beyond 54 Gy did not improve local control. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Doses greater than 50 Gy are frequently recommended for local control [15,20]. Prescribed doses for pediatric AGGs ranged between 50 and 63 Gy, but Rades et al [[8]] found that dose escalation beyond 54 Gy did not improve local control. …”
Section: Discussionmentioning
confidence: 99%
“…The extent of surgery is related to the prognosis, gross total resection being a predictor of favorable outcome with respect to both LC [3,8] and OS [6,8]. Some authors have stated that cell kinetic studies, such as MIB-1 staining, may be useful for predicting the prognosis [10,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is a debate on appropriate adjuvant treatment protocols, radiation appears to improve local tumor control (65% in radiated patients vs. 52% in patients with subtotal resection alone) for optic gangliogliomas and overall survival in low-grade tumors [34]. However, physicians must be aware of malignant transformation risk of gangliogliomas after radiation [35].…”
Section: Discussionmentioning
confidence: 99%